Efisiensi Penggunaan Faktor-Faktor Produksi pada Usaha Tani Teh Rakyat - Nanang Yusroni (AKSES: Jurnal Ekonomi dan Bisnis, 2006)
The research was  held on the argument that average of  red union on the research area, Purbalingga Regency  still under of  minimize standard of the Agricultural Instance. During the last six years  average of red union production on Purbalingga Regency was 12, 2 ton / ha each yield period, and it was under the minimize number, 20 – 40 ton/ ha each year period.  The goal of this research were knowing how far influence of   usage of production factor :  the wide of  area,  employer, seed, fertilizer, and pesticide on production and analyzing of efficiency level for production factor usage on red union cultivation on Purbalingga  Regency.The research  was done at, Bojongsari district, on Purbalingga Regency. The cross section data was used and analyze instrument  on the research was regression of Cobb Douglas production factor with multiple linear  regression on the calculation